Aplicação de revestimento cerâmico sobre diferentes substratos com blocos de alvenaria estrutural cerâmico - Nunes, Giovana Retzlaff (2018)
The growth of civil construction in recent decades has brought with it the need to reduce productive costs, promoting interventions in constructive vernacular techniques. The objective of this study was to evaluate the performance of revetment systems currently produced in the region of Santa Maria-RS, in order to build eight boxes with walls and floor (1.05m x1.05m x0.60 m) where ceramic tiles were applied on four different types of substrates applied on structural ceramic blocks of flat and rough faces, with the objective of evaluating the watertightness water in two different temperatures and steam, as well as its tensile adhesion strength. Considering the production time of the experimental models and the evaluation periods after 122 days, it can be concluded that none of the eight systems analyzed met the watertightness criteria when exposed to water at different temperatures and steam. Regarding the tensile strength of the ceramic tiles, all the same eight elements have satisfactorily met the current standards, thus demonstrating, in a contradictory way, that systems that comply with the standards ABNT NBR 13749 (2010) and NBR 13528 (2010), do not have met the requirements of ABNT NBR 15575 (2013), thus creating a risk of loss of useful life, safety of use and operation, as well as a moral, environmental and financial liability to the users and responsible for the project and execution of the building construction.